APPLICATION OF MONTMORILLONITE, ZEOLITE AND HYDROTALCITE NANOCOMPOSITE CLAYS-DRUG AS DRUG CARRIER OF SUSTAINED RELEASE TABLET DOSAGE FORM - Ainurofiq, Ahmad (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Captopril is an angiotensin converting enzyme (ACE) inhibitor asÂ antihypertensive treatment with half-life about 2h. Development of sustained-release dosage form can maintenance the drug concentration at therapeutic window in long period of time with constant release. Montmorillonite, zeolite and hydrotalcite nano-composites were used as drug carrier as sustained release dosage form. This study aimed to determine the drug release from nanocomposite of montmorillonite-drug, zeolite-drug and hydro-talcite-drug. Nanocomposite drug and carriers were made with the model drug was dispersed in carrier with matrix system. Matrices used montmorillonite, zeolite and hydrotalcite with concentrations of 20%, 30% and 40%. Characterization of matrices were done by testing the physical properties of the granules and drug release. Dissolution test using apparatus II USP model with speed rotation of 50rpm of, 900mL of HCl 0.1N as medium. The results were compared statistically with one way ANOVA 95% of interval confidence. The results showed that the difference of matrices and concentrations gave the difference effect in flow time, compact-tibility, DE360, initial burst release and maintenance release (p<0.05). Nanocomposites between drug and nanoclays occurred after 60min were shown with decreasing the drug release rate. Nanocomposite was formed with the drug molecules adsorb on nanoporous of carrier material. Increasing of clays concentration improved the fluidity and compactibility, reduced the drug release.